Mortality and Clinical Predictors After Percutaneous Mitral Valve Repair for Secondary Mitral Regurgitation: A Systematic Review and Meta-Regression Analysis - Shi, Wence; Zhang, Wenchang; Zhang, Da; Ye, Guojie; Ding, Chunhua (Frontiers in Cardiovascular Medicine, 2022)
Background: Percutaneous mitral valve repair (PMVR) provides an available choice for patients suffering from secondary mitral regurgitation (SMR), especially those whose symptoms persist after optimal, conventional, heart-failure therapy. However, conflicting results from clinical trials have generated a problem in identifying patients who will benefit the most from PMVR. Objective: To pool mortality data and assess clinical predictors after PMVR among SMR patients. To this end, subgroup and meta-regression analysis were additionally performed. Methods: We searched PubMed, EMBASE and Cochrane databases and 13 studies were finally included for meta-analysis. Estimated mortality and 95% confidence intervals (CIs) were obtained using a random-effects proportional meta-analysis. We also carried out meta-regression analysis to clarify the potential influence of important covariates on mortality. Results: A total of 1259 SMR patients who had undergone PMVR were enrolled in our meta-analysis. The long term estimated pooled mortality of PMVR was 19.3% (95% CI: 13.6 to 25.1). Meta-regression analysis showed that mortality was directly proportional to cardiac resynchronization therapy (CRT) (β= 0.009; 95% CI: 0.002 to 0.016; p=0.009), an effective regurgitant orifice (ERO) (β= 0.009; 95% CI: 0.000 to 0.018; p=0.047) and a mineralocorticoid receptor antagonist (MRA) use (β= -0.015; 95% CI: -0.023 to -0.006; p<0.001). Subgroup analysis indicated that patients with pre-existing AF (β= -0.002; 95% CI: -0.005 to -0.000; p=0.018) were associated with decreased mortality if they received a mitral annuloplasty device. Among the edge-to-edge repair device group, a higher left ventricular (LV) ejection fraction, or lower LV end-systolic diameter, LV end-systolic volume, and LV end-diastolic volume were proportional to lower mortality. Conclusions and relevance: The pooled mortality of PMVR was 19.3% (95% CI: 13.6 to 25.1). Further meta-regression indicated that AF was associated with a better outcome in conjunction with the use of a mitral annuloplasty device, while better LV functioning predicted a better outcome after the implantation of an edge-to-edge repair device.